Diagnostico de el comportamiento de la demanda de energía eléctrica en la empresa puertas induce del ecuador de la ciudad de Latacunga sector Tandalivi para determinar Parámetros de eficiencia energética. Diseño de un plan de mejoras para el portador eléctrico. - Quintana Hoyos, Enver Rodrigo (2017)
The issue of saving and efficient use of energy, under the concept of Energy Efficiency, is a resource that takes effect as a result of the problems of global warming generated as a consequence of the environmental pollution of greenhouse gases whose object is framed in the proposal of solutions and application of measures to redeem and stop the environmental deterioration of the planet ...